2011
DOI: 10.1111/j.1654-1103.2011.01297.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term vegetation changes in bogs exposed to high atmospheric deposition, aerial liming and climate fluctuation

Abstract: Questions: Is vegetation composition of ombrotrophic bogs with an undisturbed water regime resistant or sensitive to ongoing high atmospheric deposition and climatic changes? Location: The Sudeten Mountains (Czech Republic). Methods: Species composition of bryophytes and vascular plants was sampled in 25 permanent plots in suboceanic bogs of the Jizerské hory Mountains and in 26 permanent plots in subcontinental bogs of the Hrubý Jeseník Mountains. The permanent plots were established and first sampled in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 61 publications
(90 reference statements)
0
37
0
Order By: Relevance
“…The peat bog vegetation proved resilient to transient drought effects despite positive effects of increased tree cover on vascular plant transpiration and N mineralization as well as the negative effects on moss growth under drier and shaded conditions. Vegetation monitoring in some European peat bogs also suggested resilience to drought events (Gunnarsson & Flodin, ; Hajkova et al ., ). Gunnarsson & Flodin () observed reductions in tree cover and increases in Sphagnum cover during 6 years with normal precipitation that followed the dry 1995–1997 period, which suggests recovery after drought events as in our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The peat bog vegetation proved resilient to transient drought effects despite positive effects of increased tree cover on vascular plant transpiration and N mineralization as well as the negative effects on moss growth under drier and shaded conditions. Vegetation monitoring in some European peat bogs also suggested resilience to drought events (Gunnarsson & Flodin, ; Hajkova et al ., ). Gunnarsson & Flodin () observed reductions in tree cover and increases in Sphagnum cover during 6 years with normal precipitation that followed the dry 1995–1997 period, which suggests recovery after drought events as in our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…PERMDISP compares variation in measures of assemblage similarity between groups, with low dispersion indicating more homogeneous assemblages across sites within that group whereas groups with more variable assemblage similarity measures have more heterogeneous avian assemblages, with greater β diversity. PERMDISP has previously been used to analyze various biotic communities such as vegetation communities [35], soil fungal communities [36], soil seed-bank communities [37], and marine benthic communities [38], [39]; although the method appears to have not been used for the analysis of biotic homogenization of avian communities. PERMDISP tests the homogeneity of multivariate dispersions within factor groups based on deviations from the group centroid.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the study of permanent plots in our study area found that the species composition of ombrotrophic bog vegetation is relatively stable, even if environmental conditions, including water level, fluctuate considerably (Hájková et al. ).…”
Section: Discussionmentioning
confidence: 68%